Geostatistical modelling of physico-chemical properties of soils impacted by artisanal gold mining and farming: implications for soil environmental quality assessment - Kadidiatou Coulibaly; Aboubakar Sako (Sustainable Environment)
In this study, geostatistical techniques were used to investigate spatial variability of physico-chemical properties of soil samples from farming- and artisanal gold mining-affected areas. Based on coefficients of variation, chemical properties, except pH, had high variability compared to physical properties. This could be attributed to the local lithology, vegetation cover and land-use. Spatial distribution patterns of silt, clay, total nitrogen, pH and C/N could be controlled by extrinsic factors such as biological activity and land-use patterns, whereas those of electrical conductivity, organic matter (SOM) and sand were governed by both intrinsic and extrinsic factors. Because of the dominance of clay type, the distribution of cation exchange capacity (CEC) was spatially correlated with clay. About 80% of the area had acidic to circumneutral pH, which may increase mobility and toxicity of most cationic heavy metals. Distribution maps showed that microbial activities, expressed as C/N ratios, tend to be weak around farmlands, reflecting the impacts of soil management practices. In contrast, abundance of clay around the river bank is an indication of soil erosion and its redistribution from upland to depositional areas. Mean error and root mean square error of kriging were higher than those of cokriging for SOM, suggesting that cokriging was more reliable for spatial interpolation of this variable. The work reported in this study indicated that that 29%, 77% and 75% of the area had high probabilities to have pH, CEC and SOM contents below which most cationic heavy metals would be mobile and bioavailable in the soils.